Safety, efficacy and compliance of extended thromboprophylaxis in hepatobiliary and upper gastrointestinal surgery. Issue 4 (30th July 2018) - Marley, Leah; Navadgi, Suresh; Banting, Simon; Fox, Adrian; Hii, Michael; Knowles, Brett
Abstract : Background: Extended venothromboprophylaxis (eVTP) after abdominal surgery for hepatobiliary (HPB) and upper gastrointestinal (UGI) malignancies is recommended. Safety, efficacy and compliance within this group of surgical patients are not well described. The primary aim was to assess safety and compliance of post‐operative administration of eVTP with low molecular weight heparin. Secondary aim was to assess barriers to treatment and monitor the rate of post‐operative venous thromboembolism. Methods: A prospective observational cohort study of patients undergoing abdominal surgery for HPB or UGI malignancies was undertaken from January 2014 to June 2016. All patients were assessed for eVTP. Demographics, clinical outcomes and clinical questionnaires on discharge and at follow‐up 6 weeks post their initial surgery were used to assess the safety, compliance and efficacy of eVTP. Results: A total of 100 patients were assessed for post‐operative eVTP. Of these, 80 patients were prescribed 28 days of low molecular weight heparin. Of 80 patients, 65 (85%) patients completed the full eVTP, 11 (13%) missed 1–5 injections and only four (6%) missed 6–15 injections. In the 80 eVTP patients, there were no episodes of significant bleeding or venous thromboembolism. A total of nine (11%) patients would be unwilling to undertake eVTP again for a variety of reasons, including ease of disposal of syringes and needle phobias. Conclusion: The administration of eVTP in patients undergoing major HPB and UGI surgery is safe, with minimal morbidity and high compliance. The greatest barrier to administration is doctor prescription.